Lo sguardo dell'Altra. Donne dell'islam e nuovi femminismi orientalisti (Altre Modernità, 2012)
In post 9/11 one of the main focuses of the debate over Islam concerns the situation of women in Muslim countries. The rhetoric of Muslim women’s liberation has produced a huge wave of Islamophobia and has generated (Neo) Orientalist representations of the “oppressed” Muslim women in need of imperialist interventions. The promoters of this campaign are both Western “feminists” and “dissident” Muslim women who, by pretending to fight for  human rights, have produced a sensationalist Neo-orientalist literature based on the assumption of the existence of a unique, eternal and denigrated “Muslim woman”. This article explores some Neo-orientalist issues fabricated around the myth of “the Muslim woman” by Western women observers also with the complicity of female “native informants”.
Keywords: Muslim Women; Islamophobia; Neo Orientalism